Metode Forward chaining untuk Deteksi Gangguan Kejiwaan Dini - Bakhtiar, Muhammad Yusuf; Triyadi; Sihombing, Redo Abeputra; Fauzan Natsir (Jurnal Riset Sistem dan Teknologi Informasi, 2025)
Mental disorders are specific conditions associated with symptoms and pain that cause disruptions in psychosocial functioning. In general, people who want to diagnose mental disorders need to meet directly with a doctor. This research aims to develop an expert system that can assist in the process of diagnosing mental disorders, where this system can produce decisions equivalent to those of a doctor, so that the public no longer needs to meet a doctor directly for initial diagnosis. This research applies the forward chaining method with 5 types of disorders and 28 types of symptoms, which is a search technique that starts with known facts, then managed with existing data and applies inference rules to reach a conclusion. Thus, the application of this method has the potential to become an innovative solution in supporting the prevention and management of mental disorders from the early stages.